Endocrine and Metabolic impact of oral ingestion of a carob-pod derived natural syrup containing D-Pinitol: potential use as a novel sweetener in diabetes - Navarro, Juan Antonio; Decara, Juan; Dina, Medina; Tovar, Rubén; López-Gambero, Antonio J.; Pavón-Morón, Francisco Javier; Serrano, Antonia; De Ceglia, Marialuisa; Sanjuan, Carlos; Rodriguez-de-Fonseca, Fernando; Baixeras-Llano, Elena (EMBO, 2022)
The use of added sugars or non-nutritive sweeteners in processed foods and soft drinks are being blamed for multiple complications associated with obesity and diabetes. High fructose content contributes to obesity and liver steatosis, and excessive consumption of non-nutritive sweeteners can generate gut dysbiosis complicating the metabolic control exerted by the liver. Beyond its evolutionary significance in the selection of foods with a high glucose content as an energy source, the fact is that the consumption of sweets produces a hedonic pleasure in our brain. Then, the challenge stands at: how do we control the use of added sugars while providing a safe, palatable, sweet flavour to foods?. The present work explores an alternative approach, in humans and rodents, for sweetening through the use of a simple carob-pod-derived syrup which contains the inositol D-Pinitol. This inositol is known as an insulin sensitizer in muscle capable of keeping glycaemia while avoiding both unnecessary insulin secretion and the conversion of carbohydrates into fat depots .
Keywords: Metabolismo -- alteraciones; Edulcorantes naturales; Pinitol; sweetener; diabetes